The role of irisin and cytokines in the etiology of parotid tumors - Akyigit, Abdulvahap; Solmaz, Ozgen Arslan; Kalayci, Mehmet; Sakallioglu, Oner; Duzer, Sertac; Ozercan, Ibrahim Hanifi; Yalcin, Sinasi (Taylor & Francis Ltd, 2025)
This study explores the role of irisin and interleukins in parotid tumors by determining the tissue staining intensity of irisin, the salivary and plasma levels of irisin, and the plasma levels of IL-4, IL-6, IL-10 and TNF-alpha in individuals with parotid tumors. Forty-eight patients and forty healthy individuals were included to the study and allocated into four group. Benign Group I (pleomorphic adenoma), Group II (Warthin's tumor), Group III (mucoepidermoid carcinoma) and Group IV (benign parotid control group, healthy control group). Parotid tissue, plasma and saliva samples were collected from each of the patients with parotid tumors, while plasma and saliva samples were collected from the healthy individuals. Normal parotid tissue for histologic evaluation was obtained from unaffected areas in patients with parotid tumors. The levels of irisin in the plasma and saliva were significantly lower in the parotid tumors, while the plasma levels of IL-6 and TNF-alpha were higher in patients with parotid tumors, but no statistically significant difference in IL-4 and IL-10 levels was found. The histopathological intensity of FNDC-5/irisin staining was significantly decreased in the parotid tumor tissues when compared to the benign parotid control group with normal parotid tissue. The low histopathological tissue staining intensity and plasma and salivary levels of irisin suggest that irisin may be a protective protein in parotid tumors.
Keywords: Cytokine; irisin; parotid tumor; TNF-alpha